2007
DOI: 10.1007/s10633-007-9086-5
|View full text |Cite
|
Sign up to set email alerts
|

A 43-year-old man with reduced visual acuity and normal fundus: occult macular dystrophy—case report

Abstract: A new case with OMD is added to preceding reports. The mfERG and OCT tests are important in detection of OMD patients. It can help in differential diagnosis of amblyopia, optic nerve diseases and non-organic visual disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[1][2][3][4][5] Optical coherence tomography (OCT) showed structural changes in the outer nuclear and photoreceptor layers. [6][7][8][9][10][11] Recently, we found that dominant mutations in the RP1L1 gene were responsible for OMD. 12 The RP1L1 gene was originally cloned as a gene derived from common ancestors as a retinitis pigmentosa 1 (RP1) gene, which is responsible for 5-10% of autosomal dominant retinitis pigmentosa worldwide, on the same Chromosome 8.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Optical coherence tomography (OCT) showed structural changes in the outer nuclear and photoreceptor layers. [6][7][8][9][10][11] Recently, we found that dominant mutations in the RP1L1 gene were responsible for OMD. 12 The RP1L1 gene was originally cloned as a gene derived from common ancestors as a retinitis pigmentosa 1 (RP1) gene, which is responsible for 5-10% of autosomal dominant retinitis pigmentosa worldwide, on the same Chromosome 8.…”
mentioning
confidence: 99%
“…14% of their patients were diagnosed with occult macular dystrophy. These patients had normal examination with original unremarkable EOG, ERG studies and only careful interpretation of OCT showed localized disruption of outer retinal layers and multifocal ERG demonstrates the abnormality of central retina [12,13]. Inherited optic neuropathy is another condition sometimes diagnosed as FVL incorrectly [11].…”
Section: Discussionmentioning
confidence: 98%
“…The average age of onset in occult macular dystrophy has been reported to be in the mid-20s to mid-40s, and occult macular dystrophy in children is thought to be rare. Loss of vision in occult macular dystrophy is generally slowly progressive or may stabilize after a period of progression 15 . Progression may be closely monitored with visual fields, optical coherence tomography, and multifocal electroretinography, all of which may show progressive abnormalities in cone structure and function before patients notice greater severity of symptoms.…”
Section: Discussionmentioning
confidence: 99%